2012
DOI: 10.5812/hepatmon.5121
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis D Virus Infection Among Hepatitis B Virus Infected Patients in Qom Province, Center of Iran

Abstract: Context: Hepatitis C virus (HCV) infection is a significant cause of chronic liver disease in patients with human immunodeficiency virus (HIV) infection. Introduction of HCV direct-acting antiviral agents (DAAs) revolutionized the treatment of hepatitis C in patients with HIV/HCV co-infection. In this study, we systematically reviewed the treatment of chronic HCV infection in patients with HIV/HCV co-infection. Evidence Acquisition: In this systematic review, electronic databases including PubMed, Scopus, Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Due to global HBV vaccination programmes since the 1990s, HDV infection has been relatively well controlled in Europe, especially Western Europe [1]. In contrast, several countries in the Middle East are considered endemic regions for HDV infections [9][10][11][12][13]. Despite partial or full genome analyses of HDV reported from distinct geographical areas [14,15], there are limited data available on the molecular evolution of HDV from this region, particularly Iran [9,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Due to global HBV vaccination programmes since the 1990s, HDV infection has been relatively well controlled in Europe, especially Western Europe [1]. In contrast, several countries in the Middle East are considered endemic regions for HDV infections [9][10][11][12][13]. Despite partial or full genome analyses of HDV reported from distinct geographical areas [14,15], there are limited data available on the molecular evolution of HDV from this region, particularly Iran [9,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Also, not all the AEs related to cupping therapy are recorded or published, since there are no rigorous AE registration systems for cupping [ 11 ]. Furthermore, we have not found any case reports of hepatitis secondary to cupping therapy, even though several studies have reported that acupuncture and cupping are risk factors for HCV infection in Egypt [ 27 – 29 ] and HDV infection in Iran [ 30 ], presumably through transmission from infected needles.…”
Section: Discussionmentioning
confidence: 80%
“…[50] Globally, HDV appears in about 5% of HBV-infected individuals. [51] Patients on HD patients are at a higher risk of HDV infection. [52] HDV infection can present as a co-infection or super-infection.…”
Section: Hepatitis Delta Virus Infectionmentioning
confidence: 99%